Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Keterampilan Berpikir Kritis Pada Materi Bangun Datar Di SD Muhammadiyah 1 Babat - Zahro Mamluatul Muwafidah; Humairah Humairah; Arfian Mudayan (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on the critical thinking skills of fifth-grade students in the topic of plane figures at SD Muhammadiyah 1 Babat. The method used is quantitative with a pretest-posttest control group design. The sample consists of 44 students divided into two classes: an experimental class that received the PBL treatment and a control class that used a conventional learning model. The research instrument was an essay test based on critical thinking indicators, namely: interpretation, analysis, evaluation, and inference. The results of the data analysis using a t-test showed that there was a significant difference between the posttest results of the experimental and control classes. This finding proves that the PBL learning model has a positive effect on improving students' critical thinking skills. Therefore, PBL can be used as an alternative learning strategy to enhance students' critical thinking abilities in mathematics, particularly in the subject of plane figures.